2014
DOI: 10.1109/tcpmt.2014.2363659
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Electrical Properties of BCB-Liner Through-Silicon Vias

Abstract: Through-silicon vias (TSVs) using benzocyclobutene (BCB)-liners as the insulator have the potential for reducing the TSV capacitances and the thermal expansion stresses. This paper reports the assessments of BCB-liner TSVs with respect to thermal and electrical properties. The C-V and I-V characteristics are measured at room temperature and at an elevated temperature as high as 125°C to characterize the electrical properties of capacitance and leakage current at different temperatures. Some C-V and I-V feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Submitting the R tsv is 5 µm, t die is 0.1 µm into Eq. (9)- (14), the dependence of TCC on temperature are shown in Fig. 4.…”
Section: Temperature Coefficient Of C Tsvmentioning
confidence: 96%
See 1 more Smart Citation
“…Submitting the R tsv is 5 µm, t die is 0.1 µm into Eq. (9)- (14), the dependence of TCC on temperature are shown in Fig. 4.…”
Section: Temperature Coefficient Of C Tsvmentioning
confidence: 96%
“…A semi-analytical model of the TSV capacitance for elevated operating temperatures has been derived and verified with electrical measurements in [13]. It is found that the capacitance has insignificant changes and the capacitance hysteresis decreases with elevated temperatures of TSVs with BCB-liners in [14].…”
Section: Introductionmentioning
confidence: 92%
“…As the oxide is the important factor for affecting the electrical performance of Cu/CNT composite TSVs, reducing the oxide capacitance would be the best choice for performance optimization. It is known that the polymer liner, especially BCB material, and even air-gap have been proposed and exploited for TSV applications [21,22] . Therefore, we investigate the impacts of these techniques for performance optimization, as shown in Fig.6.…”
Section: Performance Optimizationmentioning
confidence: 99%
“…Several demonstrations of TSV insulation with low-k polymers deposited by solution techniques were also published. Various deposition technologies, including spin-coating, spraying, and vacuum-assisted spin coating, and various polymers (such as benzocyclobutene, , polypropylene carbonate, polybenzoxazole, and polyimide ,, ) have been investigated to achieve conformal polymer covering of trenches. Among these approaches, vacuum-assisted polymer filling has attracted great interest due to its filling ability of high aspect ratio trenches, but in the case of TSV, the conformality is still far from the requirements …”
Section: Introductionmentioning
confidence: 99%